Youth, political education and fake news: life or death of socio-political participation? (Research, Society and Development, 2020)
This paper aims to discuss, through a systematic literature review, about the possible implications of fake news in political formation and youth socio-political participation in contemporary times. Methodologically, the text has an exploratory qualitative approach subsidized by literature review, resorting to a systematic review of publications of studies and research involving the themes: “political education and youth”, “fake news and youth”, “political education, youth and fake news ”,“ youth, socio-political participation and fake news ”in the periods between 2005 to 2020 through the bibliographic survey carried out in the database of abstracts and citations of articles for academic newspapers / magazines Scopus, and between 2009 and 2019 through the scientific bases and research sources Scielo (Scientific Electronic Library Online), Coordination for the Improvement of Higher Education Personnel (CAPES) and Google Scholar. For discussion and analysis, the categories youth, political education and fake news were used. The results suggest that the debate about youth political formation represents the expression of new social paradigms in the contemporary world in view of the structure of functioning and performance of the production and dissemination of so-called fake news in the political field, since fake news has assumed the condition of agency polarizing opinions in the political field and impacting on the political formation of subjects, especially among young people. In addition, based on the bibliographic survey carried out, there is a need for scientific and academic productions on youth, political training and fake news, given the existence of little literature on this study approach.